Modern statistics for the life sciences - Grafen, Alan; Hails, Rosemary (Oxford University Press, 2002)
Model formulae represent a powerful methodology for describing, discussing, understanding, and performing that large part of statistical tests known as linear statistics. The book aims to put this methodology firmly within the grasp of undergraduates